Petroleum geology of Libya - Hallett, Don (Elsevier, 2016)
Libya has the largest petroleum reserves of any country in Africa and since production began in 1961 over 20 billion barrels of oil have been produced. Libya is scheduled to reach the mid-point of depletion of reserves in 2001 and this provides a timely point at which to review the state of petroleum exploration in Libya. A large amount of data has been published on the geology of Libya, but it is scattered through the literature; much of the older data has been superceded, and several of the key publications, especially those published in Libya, are difficult to find. This book repres.
Keywords: Petroleum -- Geology -- Libya.; elektronické knihy; electronic books